The epic of Gilgamesh an English version with an introduction - Sandars, N. K. (Nancy K.) (Penguin classics, 1972)
Presents an English version of the epic poem which dates from the third millenium B.C., telling of the adventures of Gilgamesh, the great king of Uruk, and his search for immortality.